Pelaksanaan Ekstensifikasi Wajib Pajak dan Intensifikasi Pajak: Upaya Peningkatan Penerimaan PPH Orang Pribadi pada KPP Pratama Duren Sawit - Maya Safira Dewi; Yessi Oktavia Suwarno (Binus Business Review, 2014)
The purpose of this study is to determine the expansion and intensification of the taxpayer and its effects on the revenue of Personal Income of Pratama Tax Office Duren Sawit Jakarta. Besides, this study aims to find out the obstacles that occur in the implementation of these activities. This study used qualitative method. Results of the research show that the expansion and intensification of taxpayer in Pratama Tax Office Duren Sawit, Jakarta, did not run optimally although the growth of the taxpayer and the tax revenues increased from 2010 to 2012. However, there was a slight decrease in tax revenues in 2012. Various efforts were made by Pratama Tax Office Duren Sawit Jakarta to maximize the implementation of the extensification and intensification of tax, such as socialization. To overcome problems occur in Pratama Tax Office Duren Sawit Jakarta, research’s suggestion is adding human resources if possible or optimization for effectiveness of the current resource to do outreach of taxpayers and expand cooperation with other parties.